MEMAHAMI DINAMIKA HUBUNGAN BERPACARAN JARAK JAUH PADA MAHASISWA UNIVERSITAS DIPONEGORO - Aisyah Nur Iswahyudi, Farah; Nur Suryanto Gono, Joyo; Rahardjo, Turnomo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The differences in distance and limitations in physical interaction experienced by couples in long-distance relationships (LDR) encourage individuals to adjust their communication patterns, emotions, and relationship maintenance strategies to achieve the desired level of closeness. Changes in the dynamics of long-distance relationships can affect the intensity of interaction and emotional closeness, which may lead to miscommunication and conflict. This research aims to understand the relationship maintenance strategies implemented by individuals in long-distance relationships, including the maintenance of the relationship, changes in communication patterns, conflicts or tensions that arise, and the resolution strategies applied. The theories used in this study are the Triangular Theory of Love, Relationship Maintenance Theory, and Relational Dialectics Theory. This research employs an interpretive paradigm with a phenomenological approach, using in-depth interviews as the data collection technique conducted with five individuals. The results of this research show that communication adjustments in relationship maintenance are carried out by individuals from the moment they begin a long-distance relationship with their partner. Each individual accommodates their partner's communication needs by utilizing various communication technologies, such as text messages, phone calls, and video calls in their daily interactions. Despite facing challenges related to physical distance and limited face-to-face interaction, individuals strive to maintain their relationship through intensive communication and efforts to sustain emotional intimacy. Each couple in an LDR applies relationship maintenance behaviors to achieve the desired ideal state, prevent conflicts, and maintain commitment within the relationship. Physical distance is not the main cause of conflict but often leads to minor miscommunications and tensions that need to be managed. Conflict resolution in LDRs is carried out through various strategies, such as compromise, increasing communication frequency, and maintaining emotional intimacy through virtual interactions.